2018
DOI: 10.1016/j.jdermsci.2018.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Association of elevated homocysteine levels and Methylenetetrahydrofolate reductase ( MTHFR ) 1298 A > C polymorphism with Vitiligo susceptibility in Gujarat

Abstract: The present findings suggest that MTHFR 1298 A > C polymorphism and, altered homocysteine and vitamin B levels might play a vital role in the precipitation of vitiligo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
28
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(35 citation statements)
references
References 85 publications
(98 reference statements)
0
28
0
3
Order By: Relevance
“…1). A final total of 5 case-control studies, which had recruited 1,703 patients with vitiligo and 1,708 controls, were included in the meta-analysis (3)(4)(5)(6)(7). Table I presents the basic characteristics of the included studies, all of which investigated the association between the MTHFR polymorphisms of C677T and A1298C and vitiligo susceptibility.…”
Section: Methods and Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1). A final total of 5 case-control studies, which had recruited 1,703 patients with vitiligo and 1,708 controls, were included in the meta-analysis (3)(4)(5)(6)(7). Table I presents the basic characteristics of the included studies, all of which investigated the association between the MTHFR polymorphisms of C677T and A1298C and vitiligo susceptibility.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…A previous meta-analysis found significantly higher homocysteine levels, but the same serum folate levels, in patients with vitiligo compared with controls (9). Elevated homocysteine levels may trigger several events related to the pathophysiology of vitiligo, including the production of inflammatory cytokines, oxidative stress, endoplasmic reticulum stress, and neo-self-antigen formation (5).…”
Section: Discussionmentioning
confidence: 96%
“…5,9,12,13 As for rs1801133 polymorphism, there were six studies evaluating the correlation of this polymorphism and vitiligo risk. 5,9,[12][13][14][15] Additionally, the MTHFR polymorphism (rs1801131, rs1801133) genotypic frequencies in all the subjects of control groups were consistent with HWE except 2 studies. 12,13 The NOS scores of included studies were ranged from 5 to 7, indicating the high quality of these studies.…”
Section: Characteristics Of Studiesmentioning
confidence: 99%
“…Recently, candidate gene association studies involving many candidate genes: ACE, AIRE, CAT, CD4, CLEC11A, COMT, CTLA4, C12orf10, DDR1, EDN1, ESR1, FAS, FBXO11, FOXD3, FOXP3, GSTM1, GSTT1, IL1RN, IL10, KITLG, MBL2, NFE2L2, PDGFRA-KIT, PTGS2, STAT4, TAP1-PSMB8, TGFBR2, TNF, TSLP, TXNDC5, UVRAG, VDR, XBP1 TNFA TNFB, IL4, NLRP1, MYG1, ICAM1, HLA SOD, CAT, GPX1, FOXO3a, SIRT1,IFNG, IL1B, PSMB8, VDR, DR4. Also some studies have shown genetic variants of DEFB1, SOD2, GSTM1/T1 genes are related with vitiligo [29][30][31][32][33][34][35]. The effect of these genes on the pathogenesis of vitiligo is not yet clear.…”
Section: Candidate Gene Association Studiesmentioning
confidence: 99%